The gruffalo - Donaldson, Julia; Scheffler, Axel (New York : Dial Books for Young Readers, 1999)
A clever mouse uses the threat of a terrifying creature to keep from being eaten by a fox, an owl, and a snake-- only to have to outwit that creature as well.
Booklist.
Publisher's Weekly.
School Library Journal.
3.2.
3.2
K-3
Keywords: Animals -- Fiction; Mice -- Fiction; Stories in rhyme; Animals -- Fiction; Mice -- Fiction; Stories in rhyme